Here comes the sun: solar-led green growth in MENA - Walters, J (Oxford Institute for Energy Studies, 2015)
When large-scale oil reserves were first discovered in Saudi Arabia in 1938, who would have believed that growth in MENA would ever have been oil led? Saudi Arabia had been declared a nation state only six years before, had few people with formal education, little infrastructure, no modern legal system, and was largely isolated from the rest of the world. A long and difficult journey to transport oil to market. Not an attractive investment location, not obvious there would be a large market. And the rest is history as they say. A history which few would pay attention to now.